PELATIHAN MANAJEMEN REFERENSI MENGGUNAKAN SOFTWARE MENDELEY UNTUK MENINGKATKAN KUALITAS KARYA ILMIAH MAHASISWA - Sekarsari Putri, Agnesi; Basuki, Agus (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Students often face issues with writing reference management when writing scientific papers. To avoid plagiarism, it is necessary to cite and include a bibliography. Quality scientific work needs to understand the appropriate scientific writing rules including reference management. Training on reference management using Mendeley needs to be given to students to produce quality scientific work. This training was held face-to-face by providing reference management material using Mendeley and accompanying students to practice directly in using Mendeley reference management. The training was attended by 258 participants. This activity includes three stages, namely planning, implementation, and evaluation. Training on using Mendeley reference management has been carried out well and according to plan. The results of the training showed that there was an increase in students' knowledge and skills in using Mendeley reference management. This training needs to be carried out within the scope of other faculties and even universities so that the entire academic community can use Mendeley reference management properly. Participants are advised to continue practicing, developing reference management skills with Mendeley, attending further training, and utilizing mentoring to produce high-quality papers and face complex academic demands.